Clinical and Radiographic Outcomes of a Monoblock Fluted Titanium Tapered Stem Following Complex and Revision Total Hip Arthroplasty - Oakley, Christian T.; Passano, Brandon; Lutes, William B.; Incavo, Stephen; Park, Kwan J.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2023)
Achieving femoral stem stability in complex primary and revision total hip arthroplasty (rTHA) cases is a challenging goal that monoblock fluted titanium tapered stems (FTTS) were designed to address. However, as more modern FTTS are developed, there are still questions regarding outcomes for these stems. The purpose of this study is to determine the radiographic and clinical outcomes of a modern monoblock FTTS. A multicenter retrospective observational study examined the hip databases of three institutions to obtain all monoblock FTTS with up to 5 years of radiographic follow-up. Stem subsidence and osteointegration were assessed on the most recent radiograph. All-cause re-revisions and survival of the stem at latest follow-up were recorded. Descriptive statistics were calculated for demographics and outcomes. Ninety-six monoblock FTTS were examined. Median clinical follow-up was 28.5 months (range: 18.0–57.8 months). Median subsidence was 1.4 mm (range: 0–15.0 mm). Sixteen (16.7%) and 3 (3.1%) stems had subsidence greater than 5 and 10 mm, respectively. Overall, thirteen hips (13.5%) required reoperations, of which 5 stems were revised (5.2%). Four stems were revised for periprosthetic joint infection (PJI), and one stem was explanted for exposure during acetabular revision. Kaplan–Meier analysis yielded an all-cause stem survivorship of 95.8% at 2 years and 88.5% at 4 years. Stem survivorship excluding septic causes for revision was 99.0% at both 2 and 4 years. Monoblock FTTS in complex primary and rTHA demonstrate encouraging clinical and radiographic results at up to 5 years of follow-up.
Keywords: revision; total hip arthroplasty; aseptic loosening; bone loss